Race and Revolution: Canada’s Victorian Labour Press and the Chinese Immigration Question - Spencer, David R. (Javnost-The Public, 2005)
In the closing years of the Victorian Age, thousands of labourers from China and the Indian subcontinent were imported into Canada to help build the new country’s infrastructure. In particular, these workers were employed laying the tracks for the cross country Canadian Pacific Railway. Although most workers professed to be only temporary wards of the state, hundreds if not thousands chose to stay in the Pacific Northwest and establish communities. This sense of permanence brought a strong reaction from Canadian labour unions most of whom adopted official policies demanding that Chinese and Asian labourers be deported from the country. The depth of their opposition appeared in many forms in the Canadian labour press of the period. It is here that one can sense precisely how emotional, irrational and racist the commentary was. The labour community, which pictured itself as the agent of reform in the country turned violently reactionary when confronted with this issue. The vitriolic racism that appears in journal after journal has done much to diminish the sense of reform to which labour subscribed in that period.